Hiring Practices of Human Resource Practitioners in Selected Mabuhay Accommodations in Top Tourist Destinations in the Philippines - Escarilla, Cherry C.; Canoy, Orbel M.; Maming, Jimmy B. (Future Science / FSH-PH Publications, 2024)
This research paper explores the complex field of modern HRM, with particular attention to the following topics: hiring process components, diversity and inclusion tactics, training and development programs, obstacles and advancements, legal and moral compliance, the critical function of HR, applicant competency evaluation, and technological integration. To give a thorough grasp of how these components come together inside a company's procedures, the research uses Yin's single-case study. Six (6) human resource practitioners from the municipality of the Mabuhay Lodging took part in this study. The study revealed several themes, including 1) the hiring process; 2) the influence of inclusion as well as diversity on organizational dynamics; 3) assessing the efficacy of development and training initiatives; 4) resolving issues; 5) guaranteeing legal and ethical compliance; 6) realizing the critical role of human resources; 7) improving the evaluation of applicant competence; and 8) investigating the consequences of integrating technology in the hiring process. The study reveals a dynamic interaction between these components, highlighting their combined importance in creating an inclusive, diverse, and growth-oriented workplace culture. The results reveal the complicated coordination human resource practitioners need to uphold morality, overcome barriers, and grow their firms using technology.